The Influence of Digital Tools on Student Engagement and Academic Outcomes Across Educational Levels - Hardiyanti, Eka; Fitriani, Vita; Ashari, Wahyu (Educia Journal, 2023)
The present research investigates the effectiveness of technology utilization within the context of educational quality enhancement for students, with respect to students’ motivation, achievement, and perceived educational outcomes. This developed a quantitative research design with respect to 500 students and 50 teachers from the primary, secondary, and tertiary institutions. Information was obtained using technology use questionnaires, students’ performance reports, and teachers’ feedback forms. The study showed that the more technology intensive a class or lesson is there is a high likelihood of having students’ participation and high academic achievement. Students who interactively used technologies today including learning management systems, interactive whiteboards, etc. found out they had better academic performance and motivation. Controlling for teacher efficacy and methods in the use of technology was also found greatly to affect students’ achievement. The quantitative data were analysed using descriptive and inferential measures such as the Pearson correlation and regression test to show how technology can enhance learning environment. These findings, therefore, join the emerging literature on technological integration and found positive impacts on various levels of education. This research underlines the importance of further professionalism as to teachers, and the use of proper technological means for improving the quality of education.